Cujo - King, Stephen, 1947- (New York : Viking Press, 1981)
A family's two-hundred-pound Saint Bernard is transformed by rabies and the insidious guidance of demonic forces into a terrifying monster.
Maine author.
Keywords: Rabies -- Fiction; Dogs -- Fiction; Horror fiction